2011
DOI: 10.1177/0884533611405790
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enteral Versus Parenteral Nutrition on Outcome of Medical Patients Requiring Mechanical Ventilation

Abstract: In mechanically ventilated patients in the medical ICU, ventilator-associated pneumonia rates, ICU and hospital lengths of stay, and ICU and hospital mortality rates of patients receiving PN are not significantly different than those in patients receiving EN, and feeding goals can more effectively be attained by PN. Yet, duration of mechanical ventilation is slightly longer in patients receiving PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 35 publications
1
32
0
1
Order By: Relevance
“…The characteristics of the patients included in our study were not much different in age and gender distribution to those patients included in the Arab study of Arabi et al .,[13] (51 years, 68% male), who studied underfeeding in 480 ICU patients receiving parenteral nutrition; or the Turkish study of Altintas et al .,[12] (58 years, 54% male), who analyzed prognostic characteristics of a sample of 71 ICU patients that required mechanical ventilation. The German study of Schneider et al .,[24] that studied low-volume enteral supplementation in ICU, had somewhat younger patients (47 years, 57% male).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The characteristics of the patients included in our study were not much different in age and gender distribution to those patients included in the Arab study of Arabi et al .,[13] (51 years, 68% male), who studied underfeeding in 480 ICU patients receiving parenteral nutrition; or the Turkish study of Altintas et al .,[12] (58 years, 54% male), who analyzed prognostic characteristics of a sample of 71 ICU patients that required mechanical ventilation. The German study of Schneider et al .,[24] that studied low-volume enteral supplementation in ICU, had somewhat younger patients (47 years, 57% male).…”
Section: Discussionmentioning
confidence: 93%
“…Observational studies have shown deleterious clinical outcomes associated with overfeeding, especially with parenteral nutrition. [12] Likewise, the major disadvantage of enteral nutrition is the risk of underfeeding, which has also been associated with increased mortality[13] and higher risk of bacteremia. [14]…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a clinical trial did not fi nd any difference in the incidence of VAP in patients receiving enteral versus parenteral nutrition [ 38 ].…”
Section: Enteral Feedingmentioning
confidence: 98%
“…12 These complications relate in particular to patients receiving total PN 15,50,51 and less frequently to patients receiving EN. 52 Hyperglycemia, liver dysfunction, infectious complications, prolonged mechanical ventilation, and increased mortality have all been associated with hypercaloric feeding. [53][54][55][56] The contribution of nonnutritional sources of energy such as propofol (1.1 kcal/mL and 0.1 g of fat/mL) and 5% dextrose (50 g of carbohydrate and 200 kcal/1000 mL) should be included as part of energy intake to avoid the adverse effects of overfeeding.…”
Section: Determining Energy and Protein Requirements Energy Requirementsmentioning
confidence: 99%